Baicalin Protects Mice from Lethal Infection by Enterohemorrhagic Escherichia coli - Zhang, Yong; Qi, Zhimin; Liu, Yan; He, Wenqi; Yang, Cheng; Wang, Quan; Dong, Jing; Deng, Xuming (Frontiers in Microbiology, 2017)
Shiga-like toxin-producing Escherichia coli (STEC) O157:H7 poses grave challenges to public health by its ability to cause severe colonic diseases and renal failure in both human and animals. Shiga-like toxins are the major pathogenic factor for some highly virulent E. coli expecially Shiga-like toxin 2. Conventional treatments such as antibiotics can facilitate the release of the toxin thus potentially exacerbate the diseases. Small molecule inhibitors and antibodies capable of neutralizing the toxins are the two major venues for the development of therapeutics against enterohemorrhagic serotype E. coli infection. While promising and potentially effective at clinical settings, these approaches need to overcome obstacles such as the limited routes of administration, responses from the host immune system, which are known to differ greatly among individuals. Our previous studies demonstrate that Baicalin (BAI), a flavonoid compound isolated from Scutellaria baicalensis protects against rStx2-induced cell cytotoxicity and also protects mice from lethal rStx2 challenges by inducing Stx2 to form inactive oligomers. In this manuscript, we present some exciting work showing that baicalin is an effective agent for therapeutic treatment of STEC O157:H7 infection.